2018
DOI: 10.1155/2018/9504807
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Multicomponent Nanoparticles with Extract of Mortiño (Vaccinium floribundum Kunth) Berry: Application on Heavy Metals Removal from Water and Immobilization in Soils

Abstract: rough preparation of multicomponent nanoparticles (MCNPs) using ferric chloride (FeCl 3 ), sodium sulfate (Na 2 SO 4 ), and the extract of mortiño fruit (Vaccinium floribundum Kunth), we dramatically improved the removal/immobilization of heavy metals from water and in soils. As-prepared nanoparticles were spherical measuring approximately 12 nm in diameter and contained iron oxides and iron sulfides in the crystal structure. Removal of copper and zinc from water using MCNPs showed high efficiencies (>99%) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…As seen in Figure 4(a) and Table 2, peaks in the range of 3650-3200 cm −1 are related to the vibrations of the −OH groups of the phenolic moiety of mortiño berry extract, positions from 1620 to 1690 cm −1 are attributed to the aldehydes (C O) of an ester sugar [27]. ese peaks in conjunction with the 1089 cm −1 peak (CO stretching) represent the amount of carbon that belongs to the extract [28]. Conversely, for the nanoparticles, peaks of C C alkene conjugate cis and benzene ring 1634.98 cm −1 can be seen [23].…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%
“…As seen in Figure 4(a) and Table 2, peaks in the range of 3650-3200 cm −1 are related to the vibrations of the −OH groups of the phenolic moiety of mortiño berry extract, positions from 1620 to 1690 cm −1 are attributed to the aldehydes (C O) of an ester sugar [27]. ese peaks in conjunction with the 1089 cm −1 peak (CO stretching) represent the amount of carbon that belongs to the extract [28]. Conversely, for the nanoparticles, peaks of C C alkene conjugate cis and benzene ring 1634.98 cm −1 can be seen [23].…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%
“…Hence, chemical adsorption plays an important role on the heavy metals’ adsorption using Technosols. In previous research, it has been demonstrated that chemisorption of heavy metals is quite permanent and no leakage has been observed in leachate tests using multicomponent nanoparticles and soils with different aqueous extractants ( Abril et al., 2018 ). The best correlation for all of the kinetic systems studied, is the pseudo-second order model.…”
Section: Discussionmentioning
confidence: 99%
“…La aplicación de NP Fe obtenidas de extracto de bayas de Mortiño, para la inmovilización de metales pesados como Cu, Ni, Zn, Mn, Cr, Cd; tiene un resultado con un 99% de eficiencia en remoción, así mismo, demuestra que estos metales presentes en el suelo no se filtran incluso cuando fluye agua de lluvia, agua potable y agua desionizada a través del suelo. Sin embargo, la lixiviación de metales pesados es moderada cuando se usa agua ácida como solución extractora [15].…”
Section: B) Categoría Contaminantes Inorgánicos: Aportesunclassified